2008
DOI: 10.3727/096368908787648119
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Intrapancreatic Autologous Bone Marrow Stem Cells and Hyperbaric Oxygen in Type 2 Diabetes Mellitus

Abstract: The objective of this study was to determine whether the combination therapy of intrapancreatic autologous stem cell infusion (ASC) and hyperbaric oxygen treatment (HBO) before and after ASC can improve islet function and metabolic control in patients with type 2 diabetes mellitus (T2DM). This prospective phase 1 study enrolled 25 patients with T2DM who received a combination therapy of intrapancreatic ASC and periinfusion HBO between March 2004 and October 2006 at Stem Cells Argentina Medical Center Buenos Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 57 publications
1
81
1
1
Order By: Relevance
“…Several studies of T1DM have also shown that autologous nonmyeloablative hematopoietic stem cell transplantation along with high-dose immunosuppression resulted in prolonged insulin independence in the majority of patients [18][19][20]. The final pathway of beta-cell injury in both type 1 and 2 diabetes is common, involving glucotoxicity, lipotoxicity, and cytotoxic cytokines [21], leading to similar damage to the local microenvironment in the pancreas in both types of diabetes. Previous reports indicated that multipotent stem cells could promote healing of type 2 diabetic ischemic limbs [22][23][24].…”
Section: Figmentioning
confidence: 99%
“…Several studies of T1DM have also shown that autologous nonmyeloablative hematopoietic stem cell transplantation along with high-dose immunosuppression resulted in prolonged insulin independence in the majority of patients [18][19][20]. The final pathway of beta-cell injury in both type 1 and 2 diabetes is common, involving glucotoxicity, lipotoxicity, and cytotoxic cytokines [21], leading to similar damage to the local microenvironment in the pancreas in both types of diabetes. Previous reports indicated that multipotent stem cells could promote healing of type 2 diabetic ischemic limbs [22][23][24].…”
Section: Figmentioning
confidence: 99%
“…A recent prospective phase 1 study of 25 patients, evaluated the impact of autologous BMT on the metabolic control of subjects with T2D [59]. The mononuclear fraction of a buffy coat, obtained from BMSC (from iliac crest aspirates) and peripheral blood, was injected via selective cannulation of the dorsal pancreatic artery, under angiographic guidance.…”
Section: Bone Marrow Stem Cell Transplant In Type 2 Diabetesmentioning
confidence: 99%
“…However, only a few cases of stem cell-based research were performed recently [118][119][120][121][122] to develop a therapeutic option for type 2 diabetes, as type 1 diabetes has stood as the forefront. Deriving insulinsecreting β-cells from stem cells for treatment of type 1 diabetes seems relatively straightforward compared to developing an alternative treatment option for type 2 diabetes.…”
Section: Challenges and Opportunities For Adscs In Diabetesmentioning
confidence: 99%